Juridical Review of The Amount of Administrative Sanctions in the Form of Interest and Interest Rewards PP No 35 of 2023 - Tanry, Clarisa Adelia; Pakpahan, Kartina; Pakpahan, Elvira Fitriyani (International Journal of Business, Law, and Education, 2024)
This research is motivated by the tax collection system in Indonesia using the Self Assessment System. The Self Assessment System is a tax collection system in which the government gives full trust to taxpayers to calculate, deposit and report their own tax obligations. Taxpayers are considered capable of calculating taxes, able to understand the current tax regulations, and have high levels of honesty, and are aware of the importance of paying taxes. Thus, the success of tax collection depends a lot on the taxpayers themselves. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object being studied. The data source used is secondary data with quantitative data analysis. The results of this research are Article 113 of the Job Creation Law, taxpayers submit requests for interest compensation to the Head of the KPP where the Taxpayer is registered or where the PKP is confirmed. Submission of applications can be done electronically or in writing by including the Taxpayer's domestic account number. After the taxpayer submits a request for interest compensation to the KPP, no later than one month after the application for interest compensation is received in full, the KPP will process the Taxpayer's application. Interest compensation is paid by the Directorate General of Taxes by transferring it to the account of the Taxpayer who is entitled to receive the interest compensation, then the reporting of the receipt of the interest compensation is reported in the Annual SPT in the following tax yea